Meritocracy revisited : a disaggregated approach to the study of educational and occupational attainment in Britain - Cheung, SY (1997)
Using data from the National Child Development Study, this thesis seeks to examine educational and occupational attainment in Britain by applying a disaggregated approach. It studies subject choice in higher education and sectoral differences in occupational attainment. In other words, this study is about whether meritocracy operates to different extents between different sectors of the labour market. The conventional definition of meritocracy is adopted in this thesis where achieved characteristics (measured by formal qualifications obtained) form the principle criteria for allocating individuals to different social positions. Using bivariate, multivariate analysis and logistic regression, this thesis investigates the NCDS cohort's access to higher education and to different subject groups; their economic activities in 1981; their first job and 1991 job attainment. By applying cultural capital theory, this thesis demonstrates that the level of qualification, as well as the subject of study in higher education are closely related to the social and cultural background of individuals. Inequalities in the attainment of a degree qualification are not just a matter of the 'level' of attainment, but also a matter of access to certain faculties or subjects. Subject choices of students from lower social origins are limited by their class backgrounds. In contrast, there is a link between privileged backgrounds, private selective schooling and 'elite' subjects such as Medicine and Law faculties. Degrees in 'elite' subjects usually lead to 'elite' professions in the occupational world. Subject specialisation is often translated into very different outcomes, depending on whether the subject-employment relationship is a specific or diffuse one. Most job-specific degrees give the respondents some advantage at recruitment but the importance of vocational relevance erodes over time and is less important in promotion. The first job attainment (recruitment) of equally qualified people is also found to vary distinctly between industrial sectors and firm size. Moreover, when multivariate analysis was carried out for each sector, it was found that the emphasis employers place on formal qualifications varies substantially across sectors at recruitment, but more so for men than for women. The more bureaucratised administrative and professional sectors and large establishments are found to be more meritocratic (measured by the effect of formal qualifications) and the primary and services sectors are found to be the least meritocratic. However, these variations are not so notable in promotion. Another important finding is that the effect of gender varies substantially between sectors. Equally qualified women are found to be significantly worse off than men in the most bureaucratised sectors such as private administration (which consists of banking, finance, accounting and insurance). This disadvantage persisted in promotion chances. It is therefore unwarranted to conclude that the administrative sectors are in general highly meritocratic. If we take the term 'meritocracy' to refer to the use of achieved rather than ascribed criteria for selection, then the continued use of the ascribed criterion of gender renders the administrative sector unmeritocratic. This thesis concludes that meritocracy is not a process which operates uniformly throughout the different sectors of the British labour market. Since the effects of formal qualifications on promotion are similar in different sectors, education may not be adequate in measuring merit, thus this thesis also concludes that there is a need for a broader definition of meritocracy which may include hidden factors relating to 'on-the-job training' and other personal traits.